HUBUNGAN ANTARA GAYA BELAJAR DENGAN HASIL BELAJAR SISWA KELAS VI.A PADA MATA PELAJARAN ILMU PENGETAHUAN ALAM DAN SOSIAL DI SD INPRES MANGASA GOWA: HUBUNGAN ANTARA GAYA BELAJAR DENGAN HASIL BELAJAR SISWA - Rezki Utami, Dian Ramadhani; Martini; Hasan, Salim; Hakim, Ahmad; Surani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study discusses “The Relationship Between Learning Styles and Learning Results of Class VI.A Students in the Subjects of Natural and Social Sciences at SD Inpres Mangasa Gowa.” The purpose of this study is to determine whether there is a relationship between learning styles and the learning results of Class VI.A students in the subjects of Natural and Social Sciences at SD Inpres Mangasa. This research is a correlational study using a quantitative approach. The population and sample consisted of 25 students. Data collection techniques included observation, documentation, and questionnaires. The correlation technique used was the product moment. This research was conducted at SD Inpres Mangasa Gowa. The results of the study indicate that there is a significant relationship between learning styles and learning results in Natural and Social Sciences. The study showed that the calculated r value (rcalculated) was 0.643, which falls into the strong category (values between 0.60–0.799), with a calculated t value (tcalculated) of 4.023. Therefore, the null hypothesis (H₀) was rejected, and the alternative hypothesis (Hₐ) was accepted. Furthermore, the coefficient of determination was 41.3%, indicating that learning styles contribute 41.3% to learning results in Natural and Social Sciences, while the remaining percentage is influenced by other factors.